2016
DOI: 10.2494/photopolymer.29.403
|View full text |Cite
|
Sign up to set email alerts
|

Rapid X-ray Fabrication of Microstructured Polytetrafluoroethylene Substrates by Anisotropic, Pyrochemical Microetching

Abstract: We investigate the anisotropic, pyrochemical microetching of poly(tetrafluoroethylene) (PTFE) using X-ray-induced decomposition and scission initiated by synchrotron radiation. The dependence of the anisotropic, pyrochemical-etching characteristics on X-ray photon energy is investigated by comparing the etching depths produced by two beam lines with different X-ray photon energies. Higher X-rays penetrate deeper into the PTFE substrate, resulting deeper etching depth than that by low-energy X-rays. The anisotr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Due to its outstanding characteristics, it is used in various applications, e.g., as medical piping tube, for packing in chemical plants, and as coating for cables. To further expand its use, PTFE modification has been conducted using X-, γ-, α-or electron (EB) beams, or neutron radiation [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. When PTFE is irradiated by γ-rays, EB, or neutron radiation, its mechanical properties deteriorate due to the scission of the polymer main chain, -C-C- [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Due to its outstanding characteristics, it is used in various applications, e.g., as medical piping tube, for packing in chemical plants, and as coating for cables. To further expand its use, PTFE modification has been conducted using X-, γ-, α-or electron (EB) beams, or neutron radiation [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. When PTFE is irradiated by γ-rays, EB, or neutron radiation, its mechanical properties deteriorate due to the scission of the polymer main chain, -C-C- [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…These ideal characteristics make PTFE an attractive material for microsystems such as micro-electro mechanical systems (MEMS), micro total analysis systems (µTAS), and Lab-on-achip (LOC). However, PTFE microfabrication and its bulk modification are difficult owing to the outstanding thermal and chemical stability of PTFE, with most PTFE research conducted using either x−/γ−, α, electron beam (EB), or neutron radiation to date [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…The direct etching of PTFE induced by synchrotron radiation (SR) irradiation [1][2][3] and the precise process characteristics of PTFE etching using a high-energy (2-12 keV) X-ray and heat assistance have been studied extensively [4][5][6][7]. For example, tentative bubble-like structures were observed on the X-ray irradiated surface of PTFE substrates via scanning electron microscopy (SEM), and the results indicated that surface liquefaction occurred during the photolysis of bulk PTFE, with the desorption of photoproducts from the surface and subsequent degradation of the PTFE molecules [4][5][6]. Raman spectroscopy and X-ray diffraction measurements of the X-ray irradiated PTFE surfaces suggested that the chain scissions of PTFE were driven to completion [7], with confirmation that the melting temperature of the irradiated PTFE decreased because the molecular weight decreased owing to the chain scission of PTFE via X-ray irradiation, resulting in the evaporation of photoproducts from the surface.…”
Section: Introductionmentioning
confidence: 99%
“…The method can be performed by irradiating a PTFE substrate with white light that has a photon energy of below 3 keV to deposit fragments that adsorb on the surface of a Si (100) substrate. Meanwhile, the dry etching of PTFE using high-energy (2-12 keV) X-rays has also been studied [11][12][13]. X-rays are able to penetrate deeper into the PTFE substrate than photons with an energy below 3 keV, to induce chain scission of PTFE polymers.…”
Section: Introductionmentioning
confidence: 99%
“…X-rays are able to penetrate deeper into the PTFE substrate than photons with an energy below 3 keV, to induce chain scission of PTFE polymers. By utilizing the properties of high-energy X-rays, anisotropic pyrochemical etching has been proposed [12,13], which is carried out by heating an X-ray irradiated PTFE substrate. An etching depth of 1 mm can be obtained using this method.…”
Section: Introductionmentioning
confidence: 99%